The Diversity and Diameter Growth Rate of Sprouting-Type Tree in Bukit Pinang-Pinang Forest Permanent Plots - Ade Ayu Oksari; Irvan Fadli Wanda; Erizal Mukhtar; Chairul Chairul (Jurnal Biodjati, 2019)
The process of forest regeneration can take place within a certain period of time. Sprouting is a form of strategy for in adapting to its environment for success in regenerating. The Research on  the diversity and diameter growth rate of sprouting-type tree in Bukit Pinang-pinang forest permanent plots, West Sumatra was carried out from October 2012 to December 2016 in the forest of Bukit Pinang-Pinang, West Sumatra and Herbarium Department of Biology, Universitas Andalas, Padang. This research was conducted using a survey method by census. The parameters analyzed were plant species composition, Morishita Index, Mann-Whitney test, Regression and Correlation test as well as RDGR (Relative Diameter of Growth Rate). The result of experiment was found 40 species of trees sprouting type in forest permanent plot Bukit Pinang-Pinang. The pattern of sprouting type trees distribution in the study locations was found to have a clustered, random and uniform pattern. Relative Diameter Growth Rate (RDGR) of 40 sprouting types of trees in the Bukit Pinang-Pinang forest permanent plots ranged from 0.003 cm/cm/year to 0.0288 cm/cm/year. Altitude did not affect  RDGR of an individual tree sprouting type for 31 years